APLIKASI PELAYANAN JASA LAUNDRY DI ZAZI LAUNDRY BERBASIS WEB DAN NEXMO SMS API - Nanda Dwi Dzikrillah; Maulidiansyah Maulidiansyah; Mochammad Faid (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Zazi Laundry is a clothes washing service provider that was established in April 2018 and is located in Sumberanyar Village, Paiton District, has a strategic location so that every day many use Zazi Laundry services every day. Zazi laundry provides a fairly good service to customers, but currently Zazi laundry still uses a manual system and has not used an adequate service system, so to store data it still uses books. With a system that is still manual, it makes it difficult for employees or employees to make reports and customer data stored in the book is difficult to find and transactions carried out take a long time because they have to do calculations manually. Based on the problems described, it is necessary to have a Laundry Service Application System at Zazi Laundry Web-Based and Nexmo SMS API using the waterfall model development method that can simplify and speed up employees in performing services and make it easier for customers to get information related to picking up laundry and available packages. The waterfall model provides a sequential software lifeflow approach starting from the analysis, design, coding, testing, and support stages. With this application, it is hoped that services at Zazi Laundry will be more effective and efficient and make it easier for officers to confirm to customers.